Dynamic performance of floor slabs with human-structure interaction - Zheng, Xiahua. (2008)
Lightweight pre-cast flooring systems using post-tensioning to increase strength but not stiffness are increasingly popular and dynamic serviceability issues become increasing important. In particular, human sensitivity to human induced response form walking or jumping may be the governing factor on design for serviceability.